2016
DOI: 10.5812/ijp.6733
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Factors Influencing the Quality of Developmental Care in Neonatal Intensive Care Units of Tehran

Abstract: Background: Neonatal intensive care unit (NICU) developmental care refers to interventions in the infant's environment in neonatal intensive care unit to reduce environmental stresses and provide greater family-infant compatibility. Objectives: The aim of this study was to assess current developmental care performance and factors influencing implementation of this care at NICUs in Tehran, Iran. Methods: This cross-sectional study as part of a larger mixed method study assessed the quality of developmental care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 18 publications
1
7
1
Order By: Relevance
“…26 Further studies investigating the implementation of developmental care interventions into routine practice also reported that insufficient time, higher patient caseloads, lack of neonatal experience, and inadequate knowledge and skills all had a negative impact on the delivery of developmental care in the neonatal setting. [31][32][33][34][35] Enhancing individualized caregiving and promoting developmental care practice may be seen as additional rather than essential by staff members who are struggling to meet the physiological care requirements of the babies they are caring for. Despite being aware of the importance of developmental caregiving interventions, it has been reported that bedside clinicians believe that the provision of medical treatments and attending to the infant's basic physical needs for survival often outweigh consideration of their developmental needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Further studies investigating the implementation of developmental care interventions into routine practice also reported that insufficient time, higher patient caseloads, lack of neonatal experience, and inadequate knowledge and skills all had a negative impact on the delivery of developmental care in the neonatal setting. [31][32][33][34][35] Enhancing individualized caregiving and promoting developmental care practice may be seen as additional rather than essential by staff members who are struggling to meet the physiological care requirements of the babies they are caring for. Despite being aware of the importance of developmental caregiving interventions, it has been reported that bedside clinicians believe that the provision of medical treatments and attending to the infant's basic physical needs for survival often outweigh consideration of their developmental needs.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers they listed included nursing and medical colleagues, facility limitations, leadership, and a lack of parental involvement 26. Further studies investigating the implementation of developmental care interventions into routine practice also reported that insufficient time, higher patient caseloads, lack of neonatal experience, and inadequate knowledge and skills all had a negative impact on the delivery of developmental care in the neonatal setting 31–35. Enhancing individualized caregiving and promoting developmental care practice may be seen as additional rather than essential by staff members who are struggling to meet the physiological care requirements of the babies they are caring for.…”
Section: Discussionmentioning
confidence: 99%
“…12 Research exploring the practice of developmental care in different countries has been published since the early 2000s resulting in the global spread of the practice across many settings. [13][14][15][16][17][18][19][20][21] Clinician perspectives of developmental care is predominately explored through questionnaire based research designs, 14-18, 20, 21 with two studies examining qualitative perspectives through interviews. 13,19 In Sweden, a questionnaire of neonatologists (n=139) found 93% believed NIDCAP had a positive influence on the infant.…”
Section: Introductionmentioning
confidence: 99%
“…The authors cited inconsistencies in application occurred due to a lack of personal knowledge and hospital policies. 20,21 Developmental care practices are based on cumulative experience rather than education exposure, leading to variability in practice and its application. 21,21 Developmental care has been practiced in Australia since the late 1990s.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation